Pd/C-Catalyzed Intramolecular C–H Arylation for the Synthesis of Phenanthridinones and Dibenzo-α-pyrones - Zhao, Lingyu; Shen, Guodong; Zhang, Tongxin; Wang, Zhen; Liang, Yuhua (SynOpen, 2017)
Pd/C was found to be an efficient and convenient metal catalyst for intramolecular C–H arylation reactions in the synthesis of phenanthridinones and dibenzo-α-pyrones. A variety of phenanthridinones and dibenzo-α-pyrones were synthesized under the highly active catalytic system of Pd/C-KOAc-DMA in moderate to excellent yields. The high catalytic activity, high recyclability, low costs, and ease of removal of Pd/C, combined with its commercial availability, render this protocol attractive for both synthetic and industrial applications.
Keywords: Pd/C catalysis; intramolecular reactions; C–H arylation; phenanthridinones; dibenzo-α-pyrones; recyclability